2018
DOI: 10.1002/pi.5741
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multifunctional high strength, highly swellable, stretchable and self‐healable pH‐responsive ionic double network hydrogels

Abstract: The multifunctional double network (DN) soft hydrogels reported here are highly swellable and stretchable pH‐responsive smart hydrogel materials with sufficient strength and self‐healing properties. Such multifunctional hydrogels are achieved using double crosslinking structures with multiple physical and chemical crosslinks. They consist of a copolymer network of acrylamide (AM) and sodium acrylate (Na‐AA) and other reversible network of poly(vinyl alcohol)–borax complex. They were characterized by Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Similarly, another pH-responsive DN hydrogel was prepared by replacing the second network with MBA-crosslinked poly(acrylamide-co-sodium acrylate). [82] The swelling degree of hydrogel was highly affected by AAm/NaAA ratio and pH of the medium. Increasing the more hydrophilic NaAA content, increased both swelling rate and swelling degree.…”
Section: Double-network Borax-based Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another pH-responsive DN hydrogel was prepared by replacing the second network with MBA-crosslinked poly(acrylamide-co-sodium acrylate). [82] The swelling degree of hydrogel was highly affected by AAm/NaAA ratio and pH of the medium. Increasing the more hydrophilic NaAA content, increased both swelling rate and swelling degree.…”
Section: Double-network Borax-based Hydrogelsmentioning
confidence: 99%
“…second network improved mechanical properties [81] PVA/P(AAm-co-SA) -second network improved mechanical and pH-responsive properties [82] PVA/AG -AG boost self-healing and improved mechanical strength [83] LBG/Gg pH-driven shape memory ultrafast self-healing with high mechanical properties [84] PVA/CST -CST improved machinal properties [85] HA-DP Corsslinked PAAm strain sensors mussel-inspired flexible, wearable, and self-adhesive [86] Other types of borax-based hydrogels oxidized-alginate gelatin injectable in situ forming biodegradable scaffolds for cartilage regeneration and/or treatment of meniscal injuries gelatin create dynamic imine crosslinking with oxidized alginate [87][88][89] PVA/PSA/PNIPAAm thermoresponsive touch sensors PSA/PNIPAAm improved mechanical properties; induce thermo-sensitivity Although the history for the synthesis of polyol/B hydrogels, such as PVA/B [33,40] and galactomannan/B [41] hydrogels, is turned back to the 20 th century, more detailed studies have been performed on the characteristics of these hydrogels in recent years. The stability evaluation of scleroglucan (Sclg)/B hydrogels in aqueous media showed that in high acidic and high alkaline media the stability is reduced significantly.…”
Section: Neat Polyol/borax Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, chemically responsive actuators are a more appealing option for tissue engineering applications. 258,[295][296][297][298][299][300][301] Chemically responsive bioactuators often respond to ionic strength charges or pH changes. The basic understanding of polymer-polymer, polymer-solvent, and polymer-solute interactions may lead to the engineering of SyPs-based actuators that undergo mechanical and shape transformations after responding to various external stimuli.…”
Section: Chemically Responsive Actuatorsmentioning
confidence: 99%
“…However, the conductive hydrogels prepared by only using chemical bonds have the shortcomings of being hard and brittle, easy to break under pressure. Once the chemical bonds are broken, they cannot be restored, [3,4] which will reduce the mechanical properties of the hydrogel and shorten the service life. [5,6] At present, the construction of physics and chemistry double network hydrogel has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%